New alternative data storage technology when hard disk drive reach saturation - Harnsoongnoen, Supakorn (Asia-Pacific Journal of Science and Technology, 2017)
A Hard disk drive (HDD) is the currently dominant for the non-volatile memory technology. Besides, it was also found that in the last 10-20 years, there have been numerous emerging nonvolatile memory technologies proposed, the structure and operating principle different from than that. This paper provides and analyzer to new alternative data storage technology which has potential enough to be developed to displace the hard disk drive in the year 2020. The ten alternative data storage technologies are to propose consists of Ferroelectric Memory, Phase Change Memory, Resistive Memory, Magnetic Memory, Spin Transfer Torque Memory, Carbon Nanotube Memory, Probe Memory, Holographic Memory, Copper Bridge Memory and Racetrack Memory. The analysis is divided into two criteria: 1) comparison of the potential to increase the density of data storage and 2) comparison of the performance parameters, which include access time, power efficiency, endurance and retention time. A major conclusion of the study was that to compete with hard drives on a cost per terabyte basis will be challenging for alternative data storage technologies, Phase change random access memory (PCRAM) and spin transfer torque random access memory (STTRAM) appear to meet these criteria.